Optimization of chemical conditions for metabolites production by Ganoderma lucidum using response surface methodology and investigation of antimicrobial as well as anticancer activities - Tajik, Alireza; Samadlouie, Hamid Reza; Salek Farrokhi, Amir; Ghasemi, Amir (Frontiers in Microbiology, 2024)
Ganoderma lucidum (G. lucidum) is a medicinal mushroom that is known for its ability to produce compounds with physiological effects on human health. This research was undertaken to amplify the production of bioactive components of G. lucidum under optimal cultivation conditions, obtained in a submerged state and utilized in solid state fermentation, with the purpose of enhancing antimicrobial and anticancer activities. The results indicated that titanium dioxide (TiO2 NPs), magnesium oxide nanoparticles (MgO2 NPs), and B6, along with glucose syrup and CLS syrups, were the most effective for producing GA, while wheat starch and whey protein, along with MgO2 NPs and B6 vitamin, stimulated polysaccharide production using the One Factor at a Time (OFAT) method. After screening, the response surface method (RSM) statistically indicated that the media containing 42.11 g/L wheat starch with 22 g/L whey protein and 50 g/L glucose syrup with 30 g/L CSL were found to be the best conditions for polysaccharide (21.47% of dry weight biomass) and GA (20.35 mg/g dry weight biomass) production, respectively. The moss of the fruit body of G. lucidum produced under optimal GA conditions had the highest diversity in flavonoids and phenolic acids and significant antimicrobial activity against Esherichia coli (E. coli) and Bacillus subtilis (B. subtilis). In addition, the IC50 levels of shell and stem of G. lucidum were 465.3 and 485.7 μg/mL, respectively, while the moss did not reach 50% inhibition. In the end, the statistical approaches utilized in this research to elevate the levels of bioactive components in the fruiting body of G. lucidum produced a promising natural source of antimicrobial and anticancer agents.